The Influence of the use of Financial Technology and Financial Literacy on the Consumptive Behavior of Students of the Faculty of Economics and Business, Sam Ratulangi University - SENOBUA, Sriwahyuni; SONDAKH, Jullie J.; RONDONUWU, Sintje (PT Keberlanjutan Strategis Indonesia, 2023)
Currently, there are still many people who have difficulty in managing finances, including students. This can be seen from wasteful behavior and also prioritizing wants over their needs. This study aims to: (1) determine whether the use of financial technology affects the consumptive behavior of students of the Faculty of Economics and Business, Sam Ratulangi University (2) determine whether financial literacy affects the consumptive behavior of students of the Faculty of Economics and Business, Sam Ratulangi University. The method used in this thesis research is descriptive method with quantitative approach. The population in this study were active students of the Faculty of Economics and Business, Sam Ratulangi University in the 2022-2023 academic year. This study used a simple random sampling method with a sample size of 100 respondents. The data source in this study is primary data. Data collection techniques using survey methods using questionnaires as data collection instruments. The data analysis technique used in this research is multiple regression analysis using IBM SPSS version 25. The results obtained are that partially the use of financial technology has a positive and significant effect on the consumptive behavior of students of the Faculty of Economics and Business, Sam Ratulangi University and financial literacy has a negative and significant effect on the consumptive behavior of students of the Faculty of Economics and Business, Sam Ratulangi University.